Peningkatan Partisipasi Pemilih Pemula dalam Politik - Robyan Bafadal (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Political participation is a right and not an obligation for citizens. Political participation is the involvement of citizens in making general policies and determining government leaders. There are many types of political participation, from conventional to non-conventional. However, in developing countries including Indonesia, voting in general elections is the main political participation. After that, there is no more participation. In fact, participation should be carried out as long as politics and government exist. Especially for students who are classified as novice voters as agents of change and future political leaders.